(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
President of Uzbekistan Shavkat Mirziyoyev chaired a video conference on March 19 on strengthening attention to youth, attracting them to culture, arts, physical culture and sports, developing their skills in using information technology, promoting reading among young people, increasing women’s employment. . Thirty percent of the country’s population is between 14 and 30 years old. Extensive conditions have been created for them to get an education and acquire a profession. At the same time, it is important to organize meaningful leisure time for young people. The more spiritually mature young people are, the stronger their immunity against various alien vices will be